Pembelajaran Coding Menggunakan Aplikasi Scratchjr Terhadap Kreativitas dan Kemampuan Berpikir Kritis IPAS Siswa Kelas V - Ni Komang Evi Yuliantari; I Nyoman Laba Jayanta; Ni Putu Kusuma Widiastuti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Learning of Natural and Social Sciences (IPAS) in elementary schools has not been optimal in developing students’ creativity and critical thinking skills. This condition results in relatively limited cognitive engagement. This study aimed to analyze and evaluate differences in students’ creativity and critical thinking skills in IPAS through the implementation of coding-based learning using the ScratchJr application. A quantitative approach with a quasi-experimental non-equivalent post-test only control group design was employed. The subjects consisted of 31 students in the experimental group and 27 students in the control group, selected through class-level random sampling. Data were collected using questionnaires, thinking skills tests, and learning observations, and were analyzed using descriptive statistics, ANOVA, and MANOVA. The results showed that the creativity of the experimental group (M = 76.58) was higher than that of the control group (M = 60.44) and differed significantly (F = 57.773; p < 0.001). MANOVA results indicated a significant simultaneous difference (Wilks’ Λ = 0.486; F = 29.06; p < 0.001). In conclusion, ScratchJr-based coding learning strengthens students’ creativity and critical thinking skills. The implication is that this approach is relevant to be integrated as an innovative learning strategy.